Model Pengembangan Pendidikan Tinggi Islam di Indonesia - Marwan Salahuddin (Universitas Islam Negeri Mataram, 2014)
Islamic Higher Education in Indonesia has changed rapidly to adapt to changing society. They have reformed their curriculum and revised their visions to be modern educational institutions. Now the Ministry of Religious Affairs (MORA) introduces a new policy to (re)integrate a sharp dichotomy between religious and secular sciences by establishing Islamic state university. It attempts to create a model of education that is different from general state university, which does not integrate religion and science in their curricula. With the birth of Islamic state university, the concept of Islam as a complete and perfect religion can be achieved and realized. This change opens up a new hope for Muslims that they are able to develop modern education that is not lack behind their secular institutions so they can make more substantial contribution to the state and society and resolve challenges that arise in the global era.